FAKTOR-FAKTOR YANG MEMPENGARUHI KESEHATAN MENTAL MAHASISWA DI LINGKUNGAN PERGURUAN TINGGI ISLAM - Zahra Istiqamah; Arwin Wahyu Saputra (CV. Adiba Aisha Amira, 2026)
Students’ mental health is a pressing public health issue, particularly within Islamic higher education institutions, which have distinctive academic, social and religious dynamics. This study aims to analyse the influence of stress, anxiety and social support on the mental health of students at the Al-Gazali Soppeng Islamic College (STAI). The study employed a quantitative cross-sectional design using a Likert-scale questionnaire that had been tested for validity and reliability, involving 53 active students from five study programmes. Data were analysed using Spearman’s rho correlation and multiple linear regression. The results indicate that stress, anxiety and social support simultaneously have a significant effect on mental health (F = 10.363; p = 0.000), accounting for 38.8 per cent of the variance (R2 = 0.388). Partially, social support was the most dominant positive predictor (Beta = 0.396; p = 0.001), whilst anxiety had a significant negative effect (Beta = -0.296; p = 0.018); stress had no significant effect after controlling for the other two variables. These findings underscore the importance of strengthening social support based on the Islamic campus community and academic anxiety management programmes as promotive-preventive measures to safeguard students’ mental health.